SEJARAH DAN MAKNA BATU BERELIEF DI DESA MUAK KECAMATAN BATANG MERANGIN KERINCI - SULAIMAN A, Drs. Efrizal, M.Pd, Dra.Zubaidah, M.Pd (Serupa The Journal of Art Education, 2014)
The study aims to :1) describe of the history, and 2)describe of meaning of the relief stone in Muak Village subDistrict of Kerinci. The data sources are the primary andsecondary data. The data collected through the initial review, thestudy of literature, observation, interviews, documentation. Stonerelief is come from Neolithic age, purposing as a place of worshipand as a mement. the mean of the crowned man as the leader ortribal chief. Horses meaningful as mounts, vehicle, strength,freedom, and intelligence. Elephants meaningful as vehicles,towing goods, to be war, and as a symbol of strength andprotector. Snake head meaningful as venomous animals,ingenuity, cunning, and as a protector.Kata Kunci : Sejarah dan Makna Batu Berelief di Desa MuakKecamatan Batang Merangin Kerinci